(untitled) (Journal of the College of Education for Women, 2019)
The Interests of British Military in Iraq was not based upon unified vision for the Iraqi identity ,it worked on breaking that identity and deal with the different ethnic and religious minorities and tried to bring it to its side and use it and its figures in the governmental position ,the aim was to make these minorities and here to the Britain to achieve its purposes and strategies in Iraq also vowed to provoked discord social conflicts between the components of Iraqi society.However , the British military administration depended the portioning and deepen the cracks by depending on ethnic as well as religious minorities to achieve its plans in the future and plays on the string of these minorities under the pretext of defending it and its deprived rights , it was the alibi were allathurion and Kurds were used later through the use of their religious sympathies and feelings that reject the rule of majority of Arabs.This issue aimed to create conflicts and states of instabilities inside Iraq.